2018
DOI: 10.18383/j.tom.2018.00053
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Virtual Reality for Detection of Lung Nodules on Computed Tomography

Abstract: Virtual reality (VR) systems can offer benefits of improved ergonomics, but their resolution may currently be limited for the detection of small features. For detection of lung nodules, we compared the performance of VR versus standard picture archiving and communication system (PACS) monitor. Four radiologists and 1 novice radiologist reviewed axial computed tomography (CTs) of the thorax using standard PACS monitors (SM) and a VR system (HTC Vive, HTC). In this study, 3 radiologists evaluated axial lung-wind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The rendering of two-dimensional images is discussed as a possible solution to this issue [1,13]. Namely, cross-sectional images can be fused into a three-dimensional representation of data, for instance, in virtual reality (VR) [14,15], augmented reality (AR) [15,16], on stereoscopic displays [17,18], or on volumetric displays [19,20].…”
Section: Three-dimensional Visualization Methods For Radiologistsmentioning
confidence: 99%
See 4 more Smart Citations
“…The rendering of two-dimensional images is discussed as a possible solution to this issue [1,13]. Namely, cross-sectional images can be fused into a three-dimensional representation of data, for instance, in virtual reality (VR) [14,15], augmented reality (AR) [15,16], on stereoscopic displays [17,18], or on volumetric displays [19,20].…”
Section: Three-dimensional Visualization Methods For Radiologistsmentioning
confidence: 99%
“…Recently, the possible implementation of mobile stereoscopic systems (VR and AR) was discussed for education and training in diagnostic and interventional radiology [15], however, further confirmatory studies are required to prove the efficiency of the proposed methods. The first experimental assessment of VR's implementation in diagnostic radiology was conducted by Nguen et al [14]. As no significant differences were demonstrated in lung nodule detection sensitivity, the findings indicated that the VR system might be as suitable as a traditional radiology monitor in the case of the detection of lung nodules.…”
Section: Three-dimensional Visualization Methods For Radiologistsmentioning
confidence: 99%
See 3 more Smart Citations